Norrish Type I Cleavage of 9-Oxabicyclo[3.3.1]nonan-3-one : A Straightforward Synthesis of (±)-(cis-6-Methyletrahydropyran-2-yl)acetic Acid, a Constituent of Civet - OKUMURA, Masafumi; MURAOKA, Osamu; MAEDA, Tomomi; TANABE, Genzoh; WANG, Lichen (Chemical & pharmaceutical bulletin, 1995)
The photo-reaction of 9-oxabicyclo[3.3.1]nonan-3-one (2) was investigated. Upon irradiation in methanol, the ketone (2) predominantly gave the methanol adduct, 3-hydroxymethyl-9-oxabicyclo[3.3.1]nonan-3-ol (3), accompanied with photo-reduced products, exo- and endo-9-oxabicyclo[3.3.1]nonan-3-ol (4 and 5). Irradiation in water resulted in Norrish type I cleavage to give directly (cis-6-methyletrahydropyran-2-yl)acetic acid (1), a constituent of civet, in moderate yield.